MiR‐146a enhances regulatory T‐cell differentiation and function in allergic rhinitis by targeting STAT5b. Issue 2 (6th November 2021) - Zhang, Yu; Yang, Yujuan; Guo, Jing; Cui, Limei; Yang, Liping; Li, Yumei; Mou, Yakui; Jia, Chuanliang; Zhang, Luo; Song, Xicheng
Abstract: Background: MicroRNA (miR)‐146a, as an important immune regulatory factor with an anti‐inflammatory effect, plays a crucial role in regulatory T‐cell (Tregs) differentiation and function in allergic rhinitis (AR). The present study aimed to investigate the regulatory mechanism employed by miR‐146a to control Treg differentiation and function in AR. Methods: Expression of miR‐146a and STAT5b in peripheral blood mononuclear cells (PBMCs) and nasal mucosa from patients with AR was detected by qPCR and Western blotting. Tregs were quantified by flow cytometry in miR‐146a knockdown or STAT5b knockdown PBMCs. FOXP3, IL‐10, and TGF‐β levels were detected by Western blotting or ELISA in miR‐146a knockdown or STAT5b overexpressing PBMCs, as well as in STAT5b knockdown PBMCs overexpressing miR‐146a. The effect of miR‐146a on STAT5b was observed by luciferase assay and knockdown experiments. Results: Levels of miR146a and STAT5b in the nasal mucosa or PBMCs were significantly lower in the AR group than in the control group. There were significantly fewer Tregs in miR‐146a knockdown or STAT5b knockdown PBMCs compared to control PBMCs. Expression of FOXP3, IL‐10, and TGF‐β was decreased in the miR‐146a knockdown group but increased in the STAT5b overexpression group. In contrast, miR‐146a overexpression increased the levels of these factors, but knockdown of STAT5b significantly inhibited this effect. Luciferase assay and knockdown experiments showed that miR‐146a bound directly to STAT5b. Conclusions: miR‐146a enhances Treg differentiation and function in AR by positively targeting STAT5b. Abstract : miR‐146a and STAT5b expression is lower in PBMCs and nasal mucosa of AR patients. There are significantly fewer Tregs in miR‐146a knockdown or STAT5b knockdown PBMCs compared to control PBMCs. Expression of FOXP3, IL‐10, and TGF‐β is decreased in the miR‐146a knockdown cells, but increased in the STAT5b overexpression. miR‐146a controls Treg differentiation and function by binding directly to STAT5b and up‐regulating its expression. Abbreviations: AR, allergic rhinitis; FOXP3, forkhead box P3; IL‐10, interlukin‐10; miR, microRNA; PBMCs, peripheral blood mononuclear cells; STAT5b, signal transducer and activator of transcription 5b; TGF‐β, transforming growth factor‐β; Tregs, regulatory T cells